2022 44th Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2022
DOI: 10.1109/embc48229.2022.9871277
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Connectivity for the Diagnosis of Psychogenic Non-epileptic Seizures

Abstract: Psychogenic non-epileptic seizures (PNES) are attacks that resemble epilepsy but are not associated with epileptic brain activity and are regularly misdiagnosed. The current gold standard method of diagnosis is expensive and complex. Electroencephalogram (EEG) analysis with machine learning could improve this.A k-nearest neighbours (kNN) and support vector machine (SVM) were used to classify EEG connectivity measures from 48 patients with PNES and 29 patients with epilepsy. The synchronisation method -correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Researchers have employed machine learning (i.e., artificial intelligence, AI) without explicit prespecification to try and improve the diagnostic value of investigations [14]. Hinchcliffe et al [15] and Lo Giudice et al [16] reported two different approaches based on the automated analysis of visually normal interictal EEG capable of discriminating between recordings from patients with PNES and ES.…”
Section: Diagnostic Processmentioning
confidence: 99%
“…Researchers have employed machine learning (i.e., artificial intelligence, AI) without explicit prespecification to try and improve the diagnostic value of investigations [14]. Hinchcliffe et al [15] and Lo Giudice et al [16] reported two different approaches based on the automated analysis of visually normal interictal EEG capable of discriminating between recordings from patients with PNES and ES.…”
Section: Diagnostic Processmentioning
confidence: 99%